Estimativa da produção de biomassa em populações de figueira da índia (Opuntia ficus-indica (L.) Mill.) - Reis, C.M.G. (2013)
Estimativa da produção de biomassa em populações de figueira da índia (Opuntia ficus-indica (L.) Mill).